STRATEGIES IN L2 LEARNING - Fadhilah, Ma’rifatul (VISION, 2014)
ABSRACT There are three factors influencing successful L2 learning. They are aptitude, motivation, and opportunities. Modern Language Aptitude Test has suggested three linguistics aspects which may lead to language learning success: (1) phonetic coding ability âthe ability to perceiveÂ and memorise new sounds, (2) grammatical sensitivity âthe ability to demonstrate awareness of the syntacical patterning of sentences of a new language, and (3) inductive ability âthe ability to notice and identify similarities and differences in both grammatical form and meaning. Motivation can be distinguished into integrative and instrumental. Integrative motivation implies that success in learning L2 depends on a particular orientation on the part of the learner, reflects a willingness to be like representative numbers of the other language community. Instructional motivation refers to the language task characterized by desire to gain social, self-oriented recognition and economic profits as well as advantages through knowledge. Creating opportunities to develop L2 proficiency either inside or outside the classroom is another important factor in L2 learning success. L2 learners have initiatives to take advantages from every single moment to develop their TL proficiency. Since three factors relate one to another, one factor cannot be isolated with another. L2 learners who have perfect psychological factors but have no opportunities to develop them may not achieve L2 success. Key words: TL, L2 learning, SLA, L1, L2